2004
DOI: 10.1210/jc.2004-1058
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Pituitary Dysfunction after Traumatic Brain Injury

Abstract: Disorders of water balance are well recognized after traumatic brain injury (TBI), but there are no reliable data on their true prevalence in post-TBI patients. We aimed to evaluate the prevalence of posterior pituitary dysfunction in a large cohort of survivors of TBI. One hundred two consecutive patients (85 males) who suffered severe or moderate TBI were evaluated for diabetes insipidus (DI) at a median of 17 months (range 6-36 months) after the event, using the 8-h water deprivation test (WDT). Their resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
1
20

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(175 citation statements)
references
References 27 publications
2
152
1
20
Order By: Relevance
“…Diabetes insipidus was present in 2.7% of patients with PTHP (Table 6). In a recent series of 85 patients who had suffered severe or moderate TBI, studied by the water deprivation test, permanent diabetes insipidus was detected in 6.9% of patients (69). The higher frequency of permanent diabetes insipidus as compared with other studies (5, 6, 9, 30) could be explained by the presence, in five out of seven patients, of a partial defect discovered through the water deprivation test.…”
Section: Kelly Et Al (30)mentioning
confidence: 75%
See 1 more Smart Citation
“…Diabetes insipidus was present in 2.7% of patients with PTHP (Table 6). In a recent series of 85 patients who had suffered severe or moderate TBI, studied by the water deprivation test, permanent diabetes insipidus was detected in 6.9% of patients (69). The higher frequency of permanent diabetes insipidus as compared with other studies (5, 6, 9, 30) could be explained by the presence, in five out of seven patients, of a partial defect discovered through the water deprivation test.…”
Section: Kelly Et Al (30)mentioning
confidence: 75%
“…A recent retrospective review confirmed the low prevalence (2.9%) of diabetes insipidus in TBI patients admitted to the intensive care unit, and underlined that patients who developed the disease within the first 3 days after injury had a high mortality rate (68). By contrast, other authors demonstrated a high prevalence of diabetes insipidus during the acute phase post-TBI in patients admitted to a neurosurgical center (22 -26%) (49,69) and in patients with head injury damaging the chiasm (37%) (70). However, diabetes insipidus is frequently transient and can spontaneously disappear within a few days or up to 1 month (66,70,71) after the acute event, as confirmed by its low prevalence (0 -6.9%) in patients evaluated after months or years following TBI (5,6,69).…”
Section: Consequences Of Tbimentioning
confidence: 87%
“…In adults, recent prospective data suggest that the incidence of DI may be as high as 26% in the acute phase immediately following TBI, although in up to 70% of cases complete recovery from DI was achieved within 12 months (43). Overall, the incidence of DI persisting beyond 3-12 months after TBI appears to be in the region of 7-8% in adult survivors, with many cases exhibiting a partial form of DI with mild, subclincial symptoms, which are at risk of being overlooked and undiagnosed (6,44). Post-TBI related DI may also be related to the severity of head injury event, with those patients the lower GCS ratings being more likely to develop permanent DI (44,45).…”
Section: Diabetes Insipidus Following Tbimentioning
confidence: 99%
“…Other signaling mechanisms could include trans-synaptic (Koliatsos et al, 2004) as well as anterograde and retrograde neuronal degeneration from the site of injury to the more distal sites (Sorensen et al, 1996;Bechmann and Nitsch, 1997), also eventually affecting some of the endocrine functions. While we know something about the effects of TBI on endocrine function based on human studies (Ceballos, 1966;Agha et al, 2004aAgha et al, , 2004bAgha et al, , 2005aAgha et al, , 2005bAimaretti et al, 2004Aimaretti et al, , 2005bBondanelli et al, 2004;Herrmann et al, 2006;Powner et al, 2006;Schneider et al, 2006;Tanriverdi et al, 2006), there is still some uncertainty about the mechanisms by which long-term alterations in the endocrine system (like suppression of serum GH in TBI subjects) evolve over time, and whether such changes could be prevented by therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%